Effects of Monetary Incentives on Engagement in the PACE Parenting Program - Dumas, Jean E. (2010)
This study evaluated parental engagement in an 8-week parenting program offered through daycare centers that were randomly assigned to a monetary incentive or non-incentive condition. Of an initial sample of 1,050 parents who rated their intent to enroll in the program, 610 went on to enroll, 319 in the incentive and 291 in the non-incentive condition. Results showed that intent to enroll predicted enrollment irrespective of condition. Further, parents did not enroll in greater numbers, attend more sessions or participate more actively in the incentive condition. Incentives encouraged some parents, often younger and socioeconomically disadvantaged, to enroll but had no effect on their attendance. Importantly, these results could not be accounted for by between-condition differences in child and family or in daycare characteristics.